Employee Performance is Assessed from Experience, Work Period, Training and Education Level - Kusala Dewi; Bambang Mursito; Kartika Hendra TS (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study was to determine whether there is a significant influence between the variables of experience, length of service, training, and education level on employee performance at the Surakarta City Food Security and Agriculture Agency. This research method used a quantitative descriptive research design. The population of employees working at the Surakarta City Food Security and Agriculture Agency was 94 people. The sampling technique used in this study was purposive sampling, with 54 respondents. Data collection used a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression, processed using SPSS software. Based on the results of the hypothesis testing and the discussion, it can be concluded that experience has a positive and significant effect on employee performance at the Surakarta City Food and Agriculture Security Agency. Length of service has a positive and significant effect on employee performance at the Surakarta City Food and Agriculture Security Agency. Training has a positive and significant effect on employee performance at the Surakarta City Food and Agriculture Security Agency. Education level has a positive and significant effect on employee performance at the Surakarta City Food and Agriculture Security Agency. Keywords: employee performance, experience, length of service, training, education level